Kampus Ramah Mahasiswa dari Kekerasan Seksual: Analisis Tingkat Pengetahuan Mahasiswa Terkait Pencegahan dan Penanganan Kekerasan Seksual - Anggi Yus Susilowati (UIN Siber Syekh Nurjati Cirebon, 2022)
This study aims to describe students' knowledge regarding forms of sexual violence, prevention and handling of sexual violence in analyzing the challenges of handling sexual violence in the educational environment to create a student-friendly campus from sexual violence. The research method used is quantitative with a descriptive approach. The population of this study were all students of IAIN Syekh Nurjati Cirebon with purposive sampling. Data collection techniques using a questionnaire by utilizing the googleform application. The results showed that students' knowledge of the forms of sexual violence, both physical and non-physical, was very good. However, students' understanding is inversely related to the prevention and handling of violence, which is indicated by the fact that there are still many students who do not know which campus institution is responsible, the mechanism and types of services for handling sexual violence. In creating a student-friendly campus from sexual violence, IAIN Syekh Nurjati Cirebon as an educational institution that has structural and cultural responsibility needs to carry out active socialization about sexual violence, create an academic culture that is friendly to students from violence through easily accessible communication and information and prevention education. sexual violence through learning that is responsive to sexual violence issues slot okjkt mega77 spinharta login jayaslot login royal88